História natural de Mastigodryas bifossatus (Serpentes, Colubridae) em domínio subtropical no Brasil - Leite, Pedro Terra (2006)
Mastigodryas bifossatus is a large snake in the Colubrinae subfamily. It s widely distributed in open areas over the entire South America. The dissection of 224 especimens of this snake, proceeding from the southern states of Rio Grande do Sul, Santa Catarina and Paraná, stored in herpetological colections in Brazil, provides information on dietary habits, habitat use, daily and seazonal activities, sexual dimorphism and reproductive cycles of this snake in subtropical domains in Brazil. This snake eats mainly amphibians of the Leptodactylidae´s family (80%), mammals (10%) and lizards (2%). Eight percent of the items found could not be identified. There is no ontogenetic diet shift in M. bifossatus, but as the snake grows larger, the range of preys grow as well. Most specimens inhabit open areas during the day. The activity patterns are seazonal and unimodal. Adult specimens of M. bifossatus can reach average of 1115 mm in snout-vent-lenght, and female snakes are slightly bigger than male snakes. The reproductive cycle of females is seazonal, with vittelogenesis occuring from july on. Egg laying has been recorded from november to january. The average number of offsprings per clutch is 14 and there is positive correlation between clutch size and female lenght.